Luminescent dinuclear copper(i) complexes bearing 1, 4-bis(diphenylphosphino)butane and functionalized 3-(2′-pyridyl)pyrazole mixed ligands. Issue 2 (1st December 2015) - Chen, Jing-Lin; Guo, Zong-Hao; Yu, Hua-Guang; He, Li-Hua; Liu, Sui-Jun; Wen, He-Rui; Wang, Jin-Yun
Abstract : The luminescence properties of 3-(2′-pyridyl)pyrazole-based dinuclear Cu(i ) complexes can be well modulated by altering the substituent on the pyrazolyl ring. Abstract : A family of new dinuclear Cu(i ) complexes with 1, 4-bis(diphenylphosphino)butane (dppb) and functionalized 3-(2′-pyridyl)pyrazole mixed ligands has been synthesized and characterized. It is revealed that all these Cu(i ) complexes include a [Cu2 (dppb)2 ] 2+ framework with the two Cu(i ) atoms doubly bridged by a pair of dppb to generate a fourteen-membered Cu2 P4 C8 ring, and functionalized 3-(2′-pyridyl)pyrazole adopts a neutral chelating coordination mode without the N–H bond cleavage of the pyrazolyl ring. All these dinuclear Cu(i ) complexes display a relatively weak low-energy absorption in CH2 Cl2 solution, which is closely related to the variation of the Cu–N and Cu–P bonds caused by the substituent on the pyrazolyl ring. These dinuclear Cu(i ) complexes are all emissive in solution and solid states at ambient temperature, which can be well modulated through structural modification of 3-(2′-pyridyl)pyrazole. It is shown that introduction of the trifluoromethyl group into the pyrazolyl ring is helpful for enhancing the luminescence properties of Cu(i ) pyrazole phosphine complexes.